A Study of Attitude of Customer towards Shopping Malls (In Reference to Delhi and NCR) - Jain, P. K; Khan, M. Danish (Journal of Commerce and Trade, 2012)
Retailing is one of the hottest and booming sector which generating more employment after agriculture sector. Basically retailing is a linking pin who make a bridge in between producer and consumer. In this research paper we study why customer choose shopping mall, attitude of consumer towards shopping mall, how much time spent by male/female as well as what types of problem they faced in malls.After grabbing the metro cities it moves towards the tier –II cities like Surat, Lucknow, Dehradun, Bhopal, Indore, Varanasi etc. This is a positive trend for the marketers to find out the behaviour of individual while shopping in the mall based on his/her demography so, that marketing expert helpful for targets segment them.